2009
DOI: 10.1124/mol.109.061861
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Analogs and Their Metabolites Enhance TREK-1 mRNA and K+Current Expression in Adrenocortical Cells

Abstract: bTREK-1 K ϩ channels set the resting membrane potential of bovine adrenal zona fasciculata (AZF) cells and function pivotally in the physiology of cortisol secretion. Adrenocorticotropic hormone controls the function and expression of bTREK-1 channels through signaling mechanisms that may involve cAMP and downstream effectors including protein kinase A (PKA) and exchange protein 2 directly activated by cAMP (Epac2). Using patch-clamp and Northern blot analysis, we explored the regulation of bTREK-1 mRNA and K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 50 publications
4
31
0
Order By: Relevance
“…In patch clamp experiments, we found that, when included in the pipette solution at very low concentrations (i.e. Ͻ10 M), 6-Bnz-cAMP completely blocks the activity of bTREK-1 channels, even in the presence of several PKA antagonists (36).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In patch clamp experiments, we found that, when included in the pipette solution at very low concentrations (i.e. Ͻ10 M), 6-Bnz-cAMP completely blocks the activity of bTREK-1 channels, even in the presence of several PKA antagonists (36).…”
Section: Discussionmentioning
confidence: 97%
“…5 show (38,39). At concentrations above 100 M, 6-Bnz-cAMP markedly enhances cortisol secretion (36). Treating bovine AZF cells with 6-Bnz-cAMP for prolonged periods failed to induce the expression of Ca v 3.2 current.…”
Section: Nps-acth But Not 8-br-camp Induces Expression Of Ca V 32 Cumentioning
confidence: 99%
See 3 more Smart Citations